Profit Sharing and Reciprocity: Theory and Survey Evidence - Thomas Cornelissen; John S. Heywood; Uwe Jirjahn (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
The 1/n problem potentially limits the effectiveness of profit sharing in motivating workers. While the economic literature suggests that reciprocity can mitigate this problem, it remains silent on the optimal degree of reciprocity. We present a representative model demonstrating that reciprocity may increase productive effort but may also increase unproductive effort such as socializing on the job. The model implies that reciprocity increases profit up to a point but decreases profit beyond that point. Using detailed survey measures of worker reciprocity, we show that the probability of receiving profit sharing takes an inverse U-shape as reciprocity increases. This supports the general implication of the model and is shown to exist for both positive and negative reciprocity and to remain when a series of ability proxies and detailed industry indicators are included.
Keywords: 330; Erfolgsbeteiligung; Leistungsmotivation; Austauschtheorie; Arbeitsverhalten; Theorie; Deutschland